Isolation and Enrichment of Bacteriophages by Membrane Filtration Immobilization Technique. Issue 1 (18th May 2018) - Ghugare, Gaurav S.; Nimkande, Vijay D.; Khairnar, Krishna
Abstract: The method described here enables rapid bacteriophage isolation and enrichment of host‐specific bacteriophages from an environmental sample. This is achieved by using a simple 0.45‐µm Millipore membrane where a specific host is immobilized on the membrane and a sample suspected of containing bacteriophages is exposed to the immobilized cells with the help of a membrane filtration unit. This filtration step facilitates host‐specific interaction of bacteriophages with the host and maximization of this interaction using a classic membrane filtration method. Under the effect of vacuum from a vacuum pump, a filter assembly provides a chance for every bacteriophage in the sample to interact with the specific host on the membrane filter. Our technique allows retaining specific bacteriophages on the membrane along with its host cells via adsorption; these adsorbed bacteriophages (along with their hosts) on a filter disc are then enriched in regular nutritive broth, tryptone soya broth (TSB), by incubation. With help of a plaque assay method, host‐specific phages of various bacterial species can be isolated, segregated, and enriched. © 2018 by John Wiley & Sons, Inc.